Stabilitas Hasil dan Daya Adaptasi Lima Padi Hibrida di Jawa Tengah - Widyastuti, Yuni; Satoto, Satoto (Jurnal Penelitian Pertanian Tanaman Pangan, 2012)
Five rice hybrids (H40, H41, H45, H57, and H63) and three check varieties (Maro, Hipa3, and IR64) were tested for their yield stability and adaptability at 7 locations in Central Java during the dry season of 2005. The experiment was arranged in a randomized block design with 4 replications. Objectives of the research were to evaluate stability and adaptability of the rice hybrids at 7 locations in Central Java. Yield stability and adaptability were determined based on the stability model of Eberhart and Russel and the adaptability criteria of Finlay and Wilkinson. Results indicated that yield potential of the five rice hybrids varied greatly, ranging from 4.92 t/ha (H41) to 6.35 t/ha (H35). Four rice hybrids yielded 2.33-8.61% higher than did IR64. The yield performances of hybrids H40, H45, H57, and H63 were stable across locations. Hybrids H40, H57, and H63 adapted well in all environments. Hybrid H45 adapted only to an optimal growth environment, while H40 adapted to sub optimal areas.